Analisis Hubungan Menonton Film Dalam Meningkatkan Minat Belajar IPS Terpadu Siswa Kelas VIII SMP Negeri 3 Medan - Amini Amini; Putri Maghfirah; Adelia Syafitri; Syahro Abidah Naiborhu; Agung Wijaya; Yeni Nur Khofifah Siregar (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
The purpose of this study was to examine: the effect of using film as a teaching material in the learning process for 8th grade students of SMP Negeri 3 Medan. The population in this study were 8th grade students of SMP Negeri 3 Medan city. The sample in this study consisted of 9 students. Data collection techniques were carried out using observation, questionnaires and documentation methods. The data analysis technique uses descriptive inferential statistical techniques which describe the collected data by means of depicting percent and using a simple regression formula to find the truth of the hypothesis, then it is concluded in a qualitative and qualitative descriptive way. The results showed that there was a positive effect on the Integrated IPS subject scores after using film media, which was indicated by an increase in semester scores after applying film media. Increasing the value of this semester will automatically increase the average value obtained by only 29.88 with a standard deviation of 6.948 and then increase to 84.40 with a standard deviation of 6.481 after using film media. Based on the results of the research above, it can be concluded that the use of film media as teaching material in learning has an effect on the learning process, especially in the field of Integrated IPS. Keywords: Film, Learning Interest, Learning Media